Penetapan Segmenting, Targeting dan Positioning pada Produk Nugget Ikan di Kelompok Pengolah dan Pemasar Mina Bakti Balerea - Cahyaningrum, Qoute Nuraini; Puspanidra, Tiara; Rejeki, Sari (Universitas Mataram, 2024)
This community service activity aims to increase the target partners’ knowledge related to potential consumer’s segmenting, targeting and positioning of fish nugget product. The scope of this community service activity is within The Mina Bakti Balerea processing and marketing group which is one part of BumDes Bhakti Kencana in Purwabakti Village, Pamijahan District, Bogor Regency. This community service program uses a survey method among the people of Bogor City and Regency eliciting responses in terms of the fish nugget product. Focused Group Discussion and workshop were caried out regarding segmenting, targeting and positioning to the Bumdes members. Members were given a questionnaire before and after the FGD and workshop. The purpose was to test their understanding of segmenting, targeting, positioning. After conducting the FGD and workshop, the results of the tests indicate there is an increase in understanding of positioning and targeting potential consumers and product positioning by 39,2%. From the discussion, the partners also agreed with the additional data presented by the community service team. The members of Bumdes agreed upon the taste, shape, and price of the nugget advocated by the community service team. The results of this progam also supported the Bumdes members to discover the name for their fish nugget brand and a new packaging.